Doodle2Clothing : a clothing design recognition and searching model from a doodle drawing - Ani, MD Fahim Afridi; Palak, Asif Zubayer; Dip, Shaikh Atisha Rahbath; Pramanik, Arnab; Medha, Tayaba Amin (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2024.